Risk management in small hydropower (SHP) projects of Uttarakhand: An innovative approach. Issue 3 (September 2020) - Roy, Neha Chhabra; Roy, N.G.
Abstract: Despite the huge investment potential in the small hydropower (SHP) sector, investors are not very enthusiastic about investing in the sector owing to the uncertainty associated with project costs. This paper negotiates a trade-off between insurance companies and investors. The risk class has been arrived at using a risk index, which is derived from investment risk analysis. The methodology adopted for risk index assessment uses the applied fuzzy logic approach. Thirty-six SHP projects are analysed, classified into various risk classes and a variable premium range is suggested. The paper supports investors in making better investment decisions, helps insurance companies arrive at variable insurance premium policies and assists policymakers by identifying sensitive pain points.